The Efficacy and Safety of Tizanidine in Treating Spasticity in Children with Cerebral Palsy - Nikkhah, Ali; Mohammadi, Mahmoud; Ashrafi, Mahmoud Reza; Zamani, Gholamreza (Iranian Journal of Child Neurology, 2011)
Objective Spastic cerebral palsy (CP) is one of the most difficult and disabling conditions that requires medical attention and treatment. The aim of this study was to assess the efficacy and safety of oral tizanidine in treating spasticity in children with spastic CP. Materials & Methods Sixty children with spastic cerebral palsy were enrolled in a double-blind, placebo-controlled, randomized clinical trial. These patients were randomly assigned to receive tizanidine or a matching placebo. Sample normalization was not performed either before or after the study in these two separate groups. Nevertheless, no significant statistical difference was found between the two concerned groups in terms of age, sex, or type of spasticity. Each patient received the treatment for 2 weeks between May 2010 and February 2011. Results Thirty-one boys and 29 girls with a mean age of 7.3 ± 3.4 years were evaluated. Our study revealed that spasticity was reduced in 50% of the patients receivingthe drug tizanidine compared to only 6.7% of the patients receiving the placebo. Additionally, 66.7% of patients reported less pain on the affected side receivingtizanidine (group A) compared to 13.3% of patients receiving the placebo (group B). No serious side effects were reported in this study. Conclusion Tizanidine is effective and safe in decreasing the spastic hypertonia associated with cerebral palsy in children. Keywords: Tizanidine; spasticity; cerebral palsy; children